Public perceptions of ocean health and marine protection: Drivers of support for Oregon's marine reserves. (15th February 2021) - Manson, Paul; Nielsen-Pincus, Max; Granek, Elise F.; Swearingen, Thomas C.
Abstract: Over the past several decades marine conservation policy has supported the implementation of protected areas in ocean and coastal environments to restrict some elements of human use for ecological benefits. The appropriate extent of protection and the allowable uses are often the subject of public debate about marine protected area policy. Local community dynamics around marine protected area designation and management have been the subject of much ocean and coastal management social science research. However, broader public opinions and attitudes about marine protected areas are not well understood and are critical for managers seeking to maintain their public trust obligations in environmental management. This paper provides a model for understanding the attitudes and beliefs that foster public support for or opposition to marine protections. We explored the relationships between awareness, attitudes and beliefs towards coastal and marine resource issues and uses, and demographics among a sample of Oregon, USA residents (n = 459), and tested their influence on support for expanding Oregon's recently established marine reserves. We found that Oregonians have relatively low familiarity with Oregon's marine reserve system, but that familiarity did not influence public support for Oregon's marine reserves. Instead public support was lower among coastal residents and those with positive attitudes towards commercial fisheries, and higher for those concerned with the ecological integrity of Oregon's ocean and supportive of some limits to human uses of the ocean. Our findings highlight the need for managers to engage both coastal communities and the general public to make a case for the value of marine protected areas in safeguarding the public trust. Highlights: Broad public support for marine conservation motivated by resource threat concerns. Fishing sector supporters may perceive marine conservation policy as a threat. The public trust requires balancing user needs while managing for public benefits. Marine conservation efforts must engage broader publics and impacted communities.